(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The study aims to identify the common fears of preschool children and their relationship to the approaches to parental treatment in South Al Batinah Governorate from their mother’s point of view. Total of (466) mothers were selected as the study sample. The researcher used the scale of common fear and the scale of parental treatment approaches. The results of the study have shown that the most common fear among the study sample was (the fear of darkness) in the first level with a rate of 75.03%, and in the second level came the item (my child is afraid to sleep alone) by 72.74%, in the third level came to the item (fear of seeing insects) with a rate of 67.59%, and the last one was (the fear of rain) with a rate of 35.26%. There is a weak and positive correlation between the approaches of parental treatment and common fears in the manners (protection and supervision, punishment, aggression, and bullying). On the other hand, there is a weak and negative correlation in the manners of (acceptance, harmony, encouragement, and support). There are no statistically significant differences at the indication level (α≤ 0.05) in terms of the mother’s level of education in Al Batinah South Governorate. There are statistically significant differences in the aggressiveness and bullying manner of the mothers’ age in favor of the group (20-35).